Introducing a New Research Design: The Multidimensional Interpretative Textual (MIT) Design. Epistemological and Methodological Foundations - Mariachiara Figura; Paola Arcadi; Ercole Vellone (Nursing Inquiry, 2026)
ABSTRACT Contemporary nursing research increasingly generates large and complex textual corpora from interviews, open‐ended surveys, clinical documentation, policy discourse and professional narratives. Although these materials contain rich representations of professional reasoning, organisational dynamics and patient experiences, their analysis remains largely confined to thematic qualitative approaches or variable‐based quantitative models, which may struggle to examine how meanings are organised across extensive corpora. This article introduces the Multidimensional Interpretative Textual (MIT) design as an epistemological and methodological framework for corpus‐based discourse analysis in nursing research, rather than a specific analytical technique or software procedure. The MIT design conceptualises discourse as a structured empirical object and examines textual data at the corpus level. By integrating multidimensional statistical formalisation with interpretive reasoning, it renders patterns in the organisation of meanings empirically observable before theoretical significance is attributed to them. The article outlines the design's epistemological foundations, analytical object and research logic and proposes principles of methodological rigour, including analytical–interpretive separation, corpus structural adequacy, procedural traceability, interpretive arguability, structural–interpretive proportionality and theoretical interpretive transferability. The MIT design thus provides nursing science with a coherent research architecture for examining and comparing recurring patterns of meaning, professional reasoning and organisational logics across empirical contexts.